Pasantía En La Empresa Hoteles Decameron - Área De Negociaciones Corporativas (Compras) (2025)
All-inclusive hotel models, such as Hotels Decameron, are major drivers for the country's tourism economy. To achieve good quality in the services they provide and also meet the expectations of their guests, these companies make important national and international purchases. The corporate negotiations area plays a fundamental role in this process, ensuring added value by taking the volume grouping and standardization driver so that purchases are completed efficiently and with the highest standards.